2017
DOI: 10.1111/arcm.12333
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Traditions: An Isotopic Study on the Changing Funerary Practices in the Dutch Iron Age (800–12 bc)

Abstract: Urnfields in the Dutch river area were replaced by cemeteries with a mixture of cremation and inhumation graves around the sixth century BC. This study provides the first biogeochemical evidence that the Iron Age communities were heterogeneous in terms of geological origins. The high percentage of non-locally born individuals (~48%) supports the hypothesis that the change in burial practice was the result of the influx of foreign people, who were being allowed to keep their own burial customs, whereas some of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Kootker 2014;Kootker et al 2017), in Oldenzaal no more than 7.8% of the investigated population might have been of non-local origin. This number, however, actually represents the absolute minimum number of migrants, as nonlocals who originated from areas with identical isotope values remain isotopically invisible (see also .…”
Section: Oldenzaal's Infrastructural Connections Compared To the Origmentioning
confidence: 93%
“…Kootker 2014;Kootker et al 2017), in Oldenzaal no more than 7.8% of the investigated population might have been of non-local origin. This number, however, actually represents the absolute minimum number of migrants, as nonlocals who originated from areas with identical isotope values remain isotopically invisible (see also .…”
Section: Oldenzaal's Infrastructural Connections Compared To the Origmentioning
confidence: 93%
“…The absence of an inquiry into migration is undoubtedly a confounding factor for our analysis, as we are unable to identify individuals with a mobility background nor to make assumptions regarding their living and working conditions before they moved to the cities. While a few bioarcheological studies on Dutch populations have addressed migration through isotope analysis (e.g., Kootker et al, 2016Kootker et al, , 2018Kootker et al, , 2019, there is currently no systematic study that has specifically examined the potential confounding effects of demographic nonstationarity in Dutch samples. Examining different populations would aid in assessing how human mobility could have influenced the health patterns of urban populations, especially the ones with significant migration history.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Cattle supported arable farming by traction and manure, provided food in the form of meat and dairy products and raw materials for clothing and artefacts; they also had an important social and status significance [6,7]. Recent studies have shown that mobility of livestock, including cattle, played a significant role in the study area during the Iron Age [8,9]. Mobility can be related to the role of cattle as an exchange medium, cattle raiding and the movement of human groups-almost certainly with their livestock [10].…”
Section: Introductionmentioning
confidence: 99%